Remediation of phenanthrene-contaminated soil by persulfate activated with Fe-Modified diatomite: kinetic and statistical approaches - Chiavone Filho, Osvaldo (2017)
An innovative diatomite-supported iron catalyst has been developed by using an impregnation process with a mixture of ferrous (Fe2+) and ferric (Fe3+) ions in the form of precipitated iron hydroxides. Raw and modified diatomite samples have been characterized by X-ray fluorescence and scanning electron microscopy. The main characterization results have revealed that modified diatomites are amorphous and have higher iron concentrations than raw diatomite. The results also indicate that the modified materials provided significant catalytic activity on phenanthrene degradation by using sodium persulfate. Satisfactory results were obtained with 45 g/L of sodium persulfate and 1 g of modified diatomite, thus degrading 98% of phenanthrene during 168 h of treatment. Kinetic and statistical approaches were developed for the remediation process herein, which have been validated with experimental data, thence yielding suitable results